Strategi Guru PAI dalam Membentuk Karakter Religius Siswa di SMA Negeri Binsus Dumai - Nur Afni Lubis; Murniyetti Murniyetti (ISLAMIKA, 2023)
PAI teachers have a role in shaping the religious character of students, therefore the strategy of PAI teachers in shaping the religious character of students needs to be considered. Because the strategies used will have an influence on the formation of students' religious character. The purpose of this study was to find out the religious character of students at Binsus Dumai State High School, to find out the strategies used by PAI teachers in shaping students' religious character, and to find out the factors that influence PAI teachers in shaping the religious character of students at Binsus Dumai State High School. This research uses qualitative methods with a case study approach. Researchers conducted research at Binsus Dumai State High School. The data collection techniques used are observation, interviews, and documents. The informants in this study were PAI teachers and students. Data analysis was carried out by interactive methods and used a credibility test, namely triangulation. The results showed that the religious character of students has been well formed, which can be seen from the daily life of students in schools where students are getting used to religious activities, applying the 7s culture, and carrying out obligations as a Muslim. PAI teachers use refraction and exemplary strategies in shaping the religious character of students.